The Fundamental Nature of Resilience of Engineered Systems. Issue 1 (16th August 2018) - Ferris, Timothy L.J.; Specking, Eric; Jackson, Scott; Parnell, Gregory; Pohl, Edward
Abstract: We take the position that an engineered system is a means to enable user capability that provides value to stakeholders and address the question of the fundamental nature of resilience of engineered systems. Therefore, resilience is concerned with the behavior of the system in the face of a disruption, in particular emphasizing the management, through system design of the system behavior and operational capability under disruptive conditions, which include adverse events outside the operational envelope of the system and conditions in which parts of the system have been damaged. We provide a definition of engineered resilience and show an approach to measure engineered resilience. By taking a philosophical approach to the understanding of resilience, we are able to show where resilience fits in the overall task of engineering systems and how this view provides coherence across the various aspects of resilience which is not otherwise provided.